Translation and the Relationship Between Critical Terminology and Linguistic Terminology - Abbi, Samir (El Omda in Linguistics and Discourse Analysis, 2018)
Modern criticism and linguistic through multiple terminology raised questions of knowledge and understanding left the reader a bit of confusion in the use and employment such as: stylistic and styles. The multiplicity of terminologies is cognitive, systematic, conceptual, practical, situational, translation and standardization what created for the researcher and the reader a sense of confusion accompanied by question of which terms are more right for choice, use and employment to reassure common and use. Given the conceptual significance of the term as a semiotic, semantic and inter-cultural structure of different cultures and languages, I made this study to talk about translation and the relationship of the criticism term to the linguistic one.